Innovation of Network Goods: A Non-Innovating Firm Will Gain - Amihai Glazer; Vesa Kanniainen; Mikko Mustonen (Center for Economic Studies and ifo Institute (CESifo), 2002)
We consider duopolists innovating and producing a good subject to network externalities, so that the reservation price of a consumer increases with aggregate consumption. The post-innovation network consists of two compatible sub-networks, with increased network valuation of the new product. When the non-innovating firm enjoys a larger profit than when neither firm innovates, free-riding on the winner's network as a public good arises. With such a network spillover, duopolists may underinvest in innovation.
Keywords: 330; network goods; free riding; innovation; telecommunications